Análisis de aplicaciones empleando la computación en la nube de tipo PaaS y la metodología ágil Scrum - Arana López, Liz Melissa (2016)
Many of the applications developed for companies and institutions demand high investment costs and an excessively long planning lead time. To provide a solution, streamlining and reducing costs deliverables, concepts of current technologies such as Cloud Computing and Agile Methodologies joined. The objective to demonstrate that applications can be developed in a much smaller traditional and approximately half of the estimated cost time. For which conducted an investigation of the applications that are being developed today in the Cloud Computing type PaaS (Platform as a Service) , the theoretical and practical concept of Agile Methodologies and explosive bonding of both to provide efficient deliverables without leave the quality required by the current market in the development of applications . The result is to demonstrate the efficiency of application development linking the concepts of Cloud Computing and Agile Methodologies (Scrum).